Advances and trends in engineering sciences and technologies III : proceedings of the 3rd International Conference on Engineering Sciences and Technologies (ESaT 2018), September 12-14, 2018, High Yatras Mountains, Tatranské Matliare, Slovak Republic /: proceedings of the 3rd International Conference on Engineering Sciences and Technologies (ESaT 2018), September 12-14, 2018, High Yatras Mountains, Tatranské Matliare, Slovak Republic. (2019) - Unknown
No abstract available